Effects of rehydration on the conidial viability of Metarhizium flavoviride mycopesticide formulations - Moore, D.; Langewald, J.; Obognon, F. (Informa UK Limited, 1997)
The rehydration of dried conidia of Metarhizium flavoviride was investigated in an attempt to increase speed of kill of locusts and grasshoppers by formulations of this fungus. Conidia were dried to 4-5% moisture content with no apparent adverse effects on viability, but rapid rehydration (by putting dried conidia directly in free water) reduced viability. Rehydration in an atmosphere of high humidity allowed dry conidia to absorb sufficient moisture to avoid imbibition damage. Rehydrating and pre-germinating conidia prior to spraying (in an oil-based formulation) on to the desert locust, Schistocerca gregaria, did not decrease the time to death, suggesting that moisture uptake by dry conidia on the desert locust cuticle is easily achieved.